Inhibitory Effect of Clove (Syzygium aromaticum) on the Growth of Penicillium citrinum and Citrinin Production. Issue 4 (22nd September 2013) - Aiko, Visenuo; Mehta, Alka
Abstract Clove was studied for its effect on the growth of Penicillium citrinum and citrinin production in culture medium and rice. The minimum concentration at which clove inhibited fungal growth and citrinin production was determined and recorded as 1.8 mg/mL in yeast extract sucrose broth. All concentrations of clove inhibited the fungal growth; however, citrinin production was inhibited significantly only at higher concentration. At 1.6 mg/mL, clove inhibited fungal growth and citrinin production by 80 and 58%, respectively; hence, this concentration was used to study the relationship between P. citrinum and citrinin production. Clove inhibited the growth of P. citrinum in culture media by 60–70%, throughout the observation period of 14 days. Along with the fungal growth inhibition, citrinin production was inhibited significantly. In rice, clove delayed the growth of Penicillium by 3 days; however, after 5 days of incubation, fungal growth and citrinin production were equivalent to the control. Practical Applications Citrinin is a nephrotoxin and found as a common contaminant in rice, wheat and red yeast rice. This study showed the potential of clove in controlling P. citrinum and citrinin in culture media and rice. As spices are commonly used in many food ingredients, clove may be recommended for use in processed and ready‐to‐eat foods as a preservative. The use of whole clove eliminates the need for extracting essential oils and is more economical.